Pemberdayaan Keluarga dalam Kesiapsiagaan Pencegahan Penularan TB Paru - Nasution, Johani Dewita; Siswati, Sri; Fitriani, Fitriani (Universitas Malahayati, 2025)
ABSTRACT Tuberculosis (TB) is a major public health problem worldwide. Complications due to TB are still very high in Indonesia. This shows that there is still very low knowledge in preventing transmission and treatment of pulmonary TB. One of the efforts made to prevent transmission of pulmonary TB is to involve families living in the same house. This study aims to produce a family empowerment model that is expected to reduce the rate of pulmonary TB transmission. This study used qualitative methods to find a model. Informants in the qualitative study totaled 11 families with family members suffering from pulmonary TB who lived in the same house. Data collection was obtained through direct observation and in-depth interviews with informants who had been determined with a thematic analysis approach. The qualitative study was conducted to explore factors affecting preparedness to prevent pulmonary TB transmission. The family empowerment model was designed from the qualitative study with the stages of exploration, analysis, and modification. The results of the study found 7 themes 18 subthemes and 51 categories based on the results of interviews and FGDs found include family knowledge about pulmonary TB, attitudes in the care of family members suffering from pulmonary TB, utilization of health services, guidelines for handling pulmonary TB by families, pulmonary TB emergency plans by families, resource mobilization by families, family support in the care of patients with pulmonary TB. This model is expected to be implemented in the TB case management program and can be applied by the Deli Serdang District Health Office and North Sumatra Province in the Communicable Disease Program towards END TB in 2030. Keywords: Preparedness, Family Empowerment, Tuberculosis (TB) ABSTRAK Tuberkulosis (TB) adalah masalah kesehatan masyarakat utama di seluruh dunia. Komplikasi akibat TB masih sangat tinggi di Indonesia. Ini menunjukkan masih sangat rendahnya pengetahuan dalam pencegahan penularan dan pengobatan TB paru. Salah satu upaya yang dilakukan untuk mencegah penularan TB paru adalah dengan melibatkankeluarga yang tinggal satu rumah. Penelitian ini bertujuan untuk menghasilkan model pemberdayaan keluarga yang diharapkan dapat menurunkan angka penularan TB paru. Penelitian ini menggunakan metode kualitatif untuk menemukan suatu model. Informan dalam studi kualitatif berjumlah 11 orang keluarga dengan anggota keluarga menderita TB paru yang tinggal serumah. Pengumpulan data diperoleh melalui observasi dan indepth interviewlangsung dengan informan yang sudah ditetapkan dengan pendekatan analisis tematik. Studi kualitatif dilakukan untuk mengeksplor faktor yang mempengaruhi kesiapsiagaan pencegahan penularan TB paru. Model pemberdayaan keluargadirancang dari studi kualitatif dengan tahapan eksplorasi, analisa, dan modifikasi. Hasil penelitian menemukan 7 tema 18 subtema dan 51 kategori berdasarkan hasil wawancara dan FGD ditemukan meliputi pengetahuan keluarga tentang TB paru, sikap dalam perawatan anggota keluarga yang menderita TB Paru, pemanfaatan pelayanan kesehatan, panduan penanganan TB Paru oleh keluarga, rencana darurat TB paru oleh keluarga, mobilisasi sumber daya oleh keluarga, dukungan keluarga dalam perawatan penderita TB paru. Model ini diharapkan dapat dilaksanakan dalam program penanganan kasus TB dan dapat diaplikasikan Dinas Kesehatan Kabupaten Deli Serdang dan Provinsi Sumatera Utara pada Program Penyakit Menular menuju END TB Tahun 2030. Kata Kunci: Kesiapsiagaan, Pemberdayaan Keluarga, Tuberkulosis (TB)